THE QUEST FOR INTELLECTUAL AND EXISTENTIAL FREEDOM IN J.M. COETZEE’S “THE MASTER OF PETERSBURG” AND “ELIZABETH COSTELLO”: A COMPARATIVE ANALYSIS - S. KUMARAN ARUL DEVARM, (The Bioscan, 2025)
This paper presents a comparative analysis of intellectual and existential freedom in J.M. Coetzee’s novels The Master of Petersburg and Elizabeth Costello. Coetzee’s protagonists grapple with the complexities of freedom as it intersects with personal grief, moral obligation, and the limits of societal norms. In The Master of Petersburg, the narrative centers on a writer’s confrontation with loss and authority in a politically repressive setting, revealing how the pursuit of autonomy is constrained by both external power and internal conflict. Elizabeth Costello, by contrast, interrogates intellectual freedom through the protagonist’s philosophical and ethical challenges, particularly concerning the writer’s responsibility to society versus individual expression. By comparing these works, this study reveals Coetzee’s layered approach to freedom, highlighting the paradoxes and responsibilities inherent in the quest for both personal and artistic liberation. The findings contribute to a deeper understanding of Coetzee’s exploration of freedom and morality, offering insights into the broader implications of narrative ethics within modern literature.